Time-stamp Incremental Checkpointing and Its Application for an Optimization of Execution Model to Improve Performance of CAPE (Informatica, 2018)
CAPE, which stands for Checkpointing-Aided Parallel Execution,is a checkpoint-based approach to automatically translate and execute OpenMP programs on distributed-memory architectures. This approach demonstrates high-performance and complete compatibility with OpenMP on distributed-memory systems. In CAPE, checkpointing is one of the main factors acted on the performance of the system. This is shown over two versions of CAPE. The first version based on complete checkpoints is too slow as compared to the second version based on Discontinuous Incremental Checkpointing. This paper presents an improvement of Discontinuous Incremental Checkpointing, and a new execution model for CAPE using new techniques of checkpointing. It contributes to improve the performance and make CAPE even more flexible.